Internal forced displacement in Ukraine as a challenge to social resilience - Malynovska, O.; Blyzniuk, V.; Borzenko, O.; Yatsenko, L. (Karagandy University of the name of academician E.A. Buketov, 2025)
The article examines internal displacement caused by large-scale aggression by the Russian Federation from the perspective of social resilience, which is a new approach. The humanitarian, economic, and social problems of displaced persons are systematized according to indicators that belong to generally accepted resilience assessment tools. The analysis led to the conclusion that forced migration is a serious challenge to stability at the level of individuals, communities, and society as a whole. In the context of a protracted war, the long-term solution to the problems of IDPs lies not only in creating conditions for their safe return to their places of permanent residence, but also in facilitating their integration into host communities. This is an extremely difficult task, which should be a priority for politicians and a subject of constant attention for civil society. Methodologically, the study is based on the use of historical, logical, comparative, and scientific abstraction methods.
Keywords: the factor of military confrontation; internal forced displacement; situation of IDPs; challenge to social resilience